(untitled) (Journal of Current and Advance Medical Research, 2015)
Background: Use of misoprostol in term pregnancy can give some adverse result. Objective: The purpose of the present study was to see the neonatal outcome among the term pregnant women. Methodology: This cohort study was carried out in the Department of Obstetrics and Gynaecology at Sir Salimullah Medical College and Mitford Hospital during the period from 1st September 2005 to 28th February 2006. Primi or second gravida patients with the gestational age between 37 weeks to 42 weeks in singleton pregnancy with cephalic presentation and not in labour who came for delivery purposes during the study period at any age were selected as study population. After proper selection of the cases, induction of labour (IOL) was done by applying Tab Misoprostol 50mcg in the posterior vaginal fornix. Purpose of induction of labour was successful when vaginal delivery occurred without any untoward side effects and without any surgical interference and with good APGAR score of the newborn. Result: A total number of 60 pregnant women were recruited in this study. 60% patients were within 23-30 years of age. This table shows that out of 43 cases of vaginal delivery 22 cases needed 1 dose of Misoprostol 21 cases needed more than 1 dose. This table shows that all the baby were live born. Among them 55 (92%) baby were healthy and 5 (8%) baby were asphyxiated. the depressed babies were well after resuscitation in usual manner and after 5" mean Apgar score was 9.46. Mean birth weight was 2.94 kg. Conclusion: There is no perinatal death in the misoprostol induced delivery; however, neonatal asphyxia is found in few cases as an adverse outcome. Journal of Current and Advance Medical Research 2015;2(1):3-6 DOI: http://dx.doi.org/10.3329/jcamr.v2i1.22579